Parallel Plating of Simulated Distal Humerus Fractures Demonstrates Increased Stiffness Relative to Orthogonal Plating With a Distal Humerus Locking Plate System. Issue 4 (April 2016) - Taylor, Phillip A.; Owen, John R.; Benfield, Charles P.; Wayne, Jennifer S.; Boardman, N. Douglas
Abstract : Objectives: This study compared the stiffness of precontoured parallel and orthogonal locking plate configurations in cyclic torsion and bending, and then extension to failure. Methods: Tests were conducted on 9 matched pairs of cadaveric humeri. A 10 mm block of bone was excised from the distal humerus metaphysis to simulate comminution, and fractures were repaired in matched fashion using parallel or orthogonal Biomet ALPS distal humerus locking plates (Biomet, Inc, Warsaw, IN). Specimens were tested at 0.5 degree per second up to ±2 N-m in internal and external rotation for 20 cycles, then in flexion and extension cantilevered bending at 1 mm/s to ±50 N, followed by bending at 1 mm/s to failure in extension. Results: Torsional stiffness of the parallel configuration group was greater than the orthogonal configuration in both internal and external rotation ( P < 0.0001). Also, stiffness in bending was significantly greater in the parallel configuration group in both flexion and extension ( P < 0.0001). In extension to failure testing, the parallel plate construct stiffness was significantly greater than the orthogonal configuration ( P < 0.005). Conclusions: The parallel plate configuration demonstrated significantly greater stiffness than the orthogonal plate configuration in torsion and bending using locked distal humerus plates. This greater stiffness may prove desirable in the postoperative management of patients with comminuted distal humerus fractures, providing a stable anatomic reconstruction of the joint to allow early range of motion.